Vanadium based lithium nickel aluminiumoxide system with good performance in lithium-ion batteries - Rajaa Shaari, H.; Sethuprakhash, V.; Basirun, Wan Jefrey (Penerbit UTM Press, 2016)
LiNixV1-x-y AlyO2, are cathode materials for lithium ion batteries which have been synthesized via carbon combustion method. Lithium nickel oxide derivatives are considered by the battery manufacturers to be very promising for application in 4V lithium-ion batteries. The objective of this study is, to successfully synthesize a lithium nickel vanadium aluminum oxide cathode which can show intercalation and de-intercalation process during cyclic voltammetry testing and a discharge capacity of above 50mAh/g. LiNi1-x-yVxAlyO2were synthesized by the carbon combustion method using acetylene carbon black as a binder. X-Ray Diffraction (XRD) reveals extra peaks related to Vanadium metal when it is added into LiNiAlO2. The intensity peak of the spectrum increased when the V content is increased. Scanning Electron Microscopy (SEM) shows the grain particles become non-spherical and flakes when more vanadium substituted for nickel in the sample. Fourier Transform Infrared (FTIR) spectroscopy analysis and Energy dispersive analysis of X-Ray (EDAX) confirmed that NO3- impurities are not present and composition in samples Galvanostatic charge/discharge data obtained illustrates a discharge capacity of 80.57mAh/g LiNi0.8V0.1Al0.1O2 and an average of 80.55mAh/g for 10 cycles whereas LiNi0.6V0.3Al 0.1O2 highest discharge capacity is 80.52mAh/g and also an average of 80.53mAh/g for 10 cycles. Voltammographs of the LiNi0.8V0.1Al0.1O2, LiNi0.7V0.2Al0.1O2 and LiNi0.6V0.3Al0.1O2 materials showed good oxidation and reduction loop at 0.05mV/s and 1 mV/s scan rate.